2013
DOI: 10.1021/ol400571j
|View full text |Cite
|
Sign up to set email alerts
|

Spirocyclic Dihydropyridines by Electrophile-Induced Dearomatizing Cyclization of N-Alkenyl Pyridinecarboxamides

Abstract: On treatment with acylating or sulfonylating agents, N-alkenyl pyridine carboxamides (N-pyridinecarbonyl enamines) undergo a dearomatizing cyclization initiated by pyridine acylation and followed by intramolecular trapping of the resulting pyridinium cation. The products are spirocyclic dihydropyridines which may be further elaborated to spirocyclic heterocycles with drug-like features.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…45 Recently, Clayden et al reported another electrophile-induced dearomatizing cyclization of N-alkenyl pyridinecarboxamides (Scheme 30, eqn (3)). 46 A range of spirocyclic dihydropyridines were obtained from a series of N-alkenylisonicotinamides incorporating variously substituted alkenes in the presence of triflic anhydride or chloroformates. The resulting products could be further elaborated to spirocyclic heterocycles with drug-like features.…”
Section: Dearomatization Of Pyridinesmentioning
confidence: 99%
“…45 Recently, Clayden et al reported another electrophile-induced dearomatizing cyclization of N-alkenyl pyridinecarboxamides (Scheme 30, eqn (3)). 46 A range of spirocyclic dihydropyridines were obtained from a series of N-alkenylisonicotinamides incorporating variously substituted alkenes in the presence of triflic anhydride or chloroformates. The resulting products could be further elaborated to spirocyclic heterocycles with drug-like features.…”
Section: Dearomatization Of Pyridinesmentioning
confidence: 99%
“…A variety of arenesulfonyl chlorides and differently substituted benzoylacetamides were tolerated, affording the corresponding dearomatized products moderate to good yields. Triflic anhydride was employed by Clayden in 2013 to promote an intramolecular spirocyclization of N-alkenyl isonicotinamides [49]. If the unactivated substrate was completely inert, upon salification of the pyridinic nitrogen into a triflate salt, the enamide moiety became nucleophilic enough to promote dearomatization, generating a 1,4-dihydropyridine displaying a spirobicyclic structure (Scheme 15).…”
Section: N-sulfonylpyridinium Saltsmentioning
confidence: 99%
“…63 Precise control of temperature has been shown to significantly affect hydrogenation chemoselectivity, e.g. 64 Selective control over olefin, furan and nitrile moiety hydrogenation has also been reported (Scheme 19). 69 Catalyst switching also effects chemoselectivity with hydrogenation of 19 using 10% Pd/C resulting in specific olefin reduction to afford 59.…”
Section: Chemoselective Olefin and Alkyne Hydrogenationmentioning
confidence: 99%
“…The significant portion of currently reported olefin reduction flow protocols employ 10% Pd/C, with sterically hindered or highly substituted bonds requiring elevated temperature or pressures (Scheme 13). 4,44,61,[63][64][65][66] As previously mentioned flow reduction of olefins has been reviewed by Irfan et al 2 and consequently discussion herein is limited to hydrogenation of olefin moieties using organometallic flow protocols, chemoselective and asymmetric olefin hydrogenations.…”
Section: Olefin Hydrogenationsmentioning
confidence: 99%